Social Media Exposure and Grammar Proficiency of Junior High School Students’: A Correlational Study - Otibar, Jennen; Egargo, Vanna; Calvara, Caryl; Macion, Karla; Abrugar, Shiela Mae; Sanchez, Alma Sonia Q.; Danday, Billy A.; Calzita, Catherine (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Social media has emerged as a contemporary form of media with diverse attributes and characteristics. It serves as a means of instruction, and the younger generation frequently engages with it for various social interactions and communication purposes. While social media offers features not limited to education and is readily accessible to students, it can also impact certain academic aspects through this new digital medium. This study investigated the association between social media exposure and grammar proficiency among junior high school students, specifically spelling and punctuation marks usage. The researchers employed a correlational design and collected quantitative data. Through, total population sampling method, students from Grades 7, 8, 9, and 10 in a laboratory school in Eastern Visayas were chosen. The questionnaire included a spelling and punctuation examination, and the results were analyze using statistical methods such as mean, percentage, standard deviation, Pearson correlation (r), and Eta – correlation. This study's findings indicate no significant relationship between the grammar proficiency of the respondents and their social media exposure, as there is a relatively low correlation and association between the time spent on social media and grammar proficiency test scores. However, the study also revealed a positive correlation between age and grammar proficiency, implying that the older the respondents, the higher their knowledge about correct spelling and punctuation marks usage. Furthermore, the study also suggests conducting further research to explore the relationship between other components of grammar competency and specific social media platforms, such as TikTok, which has the highest hours of exposure.